Prediction model for economy-driven provincial natural gas load in China - Xueping DU; Zhikai LANG; Menglin LIU; Jiangtao WU (You-qi chuyun)
In order to reasonably establish the objectives and compare the potential of development in provincial natural gas planning, innovative exploration was carried out for the natural gas load prediction model. Through data classification, correlation analysis and benchmarking analysis with the developed countries, the medium- and long-term prediction model of economy-driven provincial natural gas load in China was established by the surface fitting method. Meanwhile, the three-dimensional coordinate system of natural gas consumption potential, GDP and primary energy consumption was drawn. Ten southern provinces (municipalities directly under the Central Government) were selected as the research subjects to quantitatively analyze the natural gas consumption demand in 2030. The results indicate that there is a strong demand for natural gas in the future. Under the scenario of a compound GDP growth rate of 5%, the total demand for natural gas in the ten provinces (municipalities directly under the Central Government) will reach 3 155×108 m3 in 2030, which is 2.5 times that of 2021. Among them, Guangdong Province and Hunan Province have the largest absolute increase and the highest growth rate of consumption, respectively. Generally, the research results could provide reference for the market regulation and development of natural gas.